Collaborative Approaches and Policy Opportunities for Accelerated Progress toward Effective Disease Prevention, Care, and Control: Using the Case of Poverty Diseases to Explore Universal Access to Affordable Health Care - Laokri, Samia (Frontiers in Medicine, 2017)
There is a massive global momentum to progress towards the sustainable development and universal health coverage goals. However, effective policies to healthcare coverage can only emerge through high-quality services delivered to empowered care users by means of strong local health systems and a translational standpoint. Health policies aimed at removing user fees for a defined healthcare package may fail at reaching desired results if not applied with system thinking. Moreover, bottlenecks to effective policy persist and tend to relate to the universal coverage dimensions. Poverty diseases such as tuberculosis may constitute prime examples to assess the extent of effective high-priority healthcare coverage. Despite available financing in tuberculosis control, the new goal towards no TB-affected household experiencing catastrophic expenditure may remain aspirational. Several deficiencies in public healthcare delivery systems and financial protection mechanisms were investigated to provide an analytical framework to develop effective approaches to health, and foster system levers for integrated care. Yet, healthcare delivery performance and policy responsiveness have to do with collaborative work among all health stakeholders. Public-private mix strategies may play a role in lowering the economic burden of disease. This emphasizes possible added-value of collaborative work approaches to enhance dynamic local knowledge development and realize integration with the various healthcare silos. Further research is needed to optimize the use of locally relevant knowledge, networks and technologies. Rational decisions for efficient disease-specific control interventions will rely on a transparent evidence base that can be provided through regular assessment and monitoring of policy responsiveness to improved health goals.